(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2019)
While the world reeled from the stun result of the US Presidential Elections, on November ninth, 2016, a country of a billion of people faced an even bigger surprise as all existing currency notes of 500 and 1000 rupees would be demonetised, with immediate effect. Since November 8, every Indian is in the dilemma of picking a secure and convenient cashless payment option. The cashless payment options that are currently available include creditdebit cards, e-wallets, for example, Paytm, Mobikwik, SBI E-wallet, etc., RTGS, NEFT etc. The move of ’Demonetization’ by the Hon’ble Prime Minister of India, Mr. Narendra Modi swayed everybody on November 08, 2016. It resulted into a frenzy circumstance because people were short of money in their grasp. Demonetization impacted internet shopping at introductory phase however later the online sellers witnessed complex increase in their sales and revenue. The consequences of this led to the use of computerized payments and online exchanges in pretty much every piece of the nation. This move likewise increased the use of advanced and mobile wallets offered by different companies and banks. This unpredictable move made by the Prime Minister Narendra Modi has impacted e-commerce as well as at the same time affects the consumers and their shopping behavior through online shopping. Consequently, it becomes necessary to ponder the effect of demonetization on e-commerce industry and the purchasing propensities for the people. The principle focal point of the investigation is to understand effect of demonetization on consumer’s frequency of buying item and consumer’s mode of payment for online shopping post demonetization. The examination reveals more positive than negative effects of Demonetisation on E-commerce industry.